PENGARUH PEMAHAMAN PERPAJAKAN DAN E-FILLING TERHADAP KEPATUHAN WAJIB PAJAK PRIBADI PADA KPP PRATAMA MAKASSAR UTARA - Amalia, Riza; Lestari, Ismi Ayu (Pusat Penerbitan dan Publikasi Ilmiah FEB-UMI, 2022)
This study aims to determine the effect of understanding on taxation and e-filling on personal taxpayer compliance at Kpp Pratama North Makassar. This research method uses quantitative methods. The population of this research is the personal taxpayer of North Makassar Kpp Pratama. The sample selection was through random sampling where there were 70 samples that met the criteria as research samples. The analytical technique used in this research is multiple linear regression analysis. The results of this study prove that Tax Understanding and E-Filling have a positive and significant effect on Personal Taxpayer Compliance at North Makassar Kpp Pratama.